Sistema informatizado de valoración enfermera de la urgencia pediátrica en atención primaria VEUPAP y su enlace a la historia clínica informatizada de atención primaria. - GARCÍA HERNÁNDEZ, MARÍA NOELIA; AGUIRRE JAIME, ARMANDO (Revista ROL de Enfermería, 2020)
OBJECTIVE. Design of the informatic version of the VEUPAP system (Nurse Pediatric Emergency Assessment of Primary Care). DESIGN. The development of computer application VEUPAP followed three stages: 1. Design outputs and inputs necessary to the system to ensure those outings. 2. Data entry procedures and their programming algorithms to obtain the expected outputs. 3 Getting initial computerized version for VEUPAP, its set-up and pilot proof with modifications and adjustments to achieve final version. RESULTS. Automatized VEUPAP on personal computer with Microsoft Windows NT Professional operating system, with a general overview of the fields that comprise valuation, specificities of entries in each field and clinical report type output. CONCLUSIONS. Computerized VEUPAP linked with clinical history of primary care allows that all data process of nurse clinical activity in urgent pediatric care be transparent and accessible, allowing be known and be used by all professionals in primary care. The footprint of information generated by VEUPAP allows monitor progress and assess their impact on the nursing management of pediatric emergencies in primary care, with subsequent evaluation of the possibility of its extension to new fields. The implementation of automated VEUPAP in daily practice allows to develop areas of care nurse finalist and incorporate nursing taxonomic systems, depending on the assigned priority and considering the specific diagnosis of the patient, enable to graduate specific interventions to achieve optimal results in nursing care.